Analisis Model Two Way dalam Digital Public Relations Sendi Fardiansyah di Pilkada Kota Bogor - Rabbani Alhanan Hassim; Istisari Bulan Lageni (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The 2024 Bogor City Regional Head Election (Pilkada) is a crucial event in local political contestation, marked by the increasingly strong role of digital media in campaign strategies. This research focuses on the Analysis of the Two-Way Symmetrical Model in Sendi Fardiansyah's Digital Public Relations in the 2024 Bogor City Pilkada. The background of this research is based on the phenomenon of the increasing use of digital media as the main means of political communication, especially in regional head election campaigns. The purpose of the research is to determine how digital public relations activities are carried out by Sendi Fardiansyah's campaign team by applying a two-way symmetrical communication model, and to analyze the effectiveness of this strategy in building a political image and interacting with the public. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews with the media team, digital campaign activities, and analysis of social media content and mainstream media publications. The results show that Sendi Fardiansyah implemented strategic stages that include problem determination, program planning through a content calendar, interactive implementation of digital communication on various platforms (Instagram, Facebook, and TikTok), and program evaluation through indicators of engagement rate, reach, and public feedback.